Mapping Contextual Similarity Units for Agroecological Scaling toward Achieving Land Degradation Neutrality - Shiri, Zahra; Le, Quang Bao (International Center for Agricultural Research in the Dry Areas, 2024)
This report provides a spatial typology framework adapted to upscale agroecological practices to achieve land degradation neutrality targets. This spatial typology approach provides a classification of different complex agroecosystems through climate, soil, vegetation patterns, economic factors, etc. This typology is useful for scaling up agroecological innovations at the level of the Kef-Siliana transect, which is the case study of the present research. Both policy makers and practitioners can benefit from this typology to address the issues related to climate, landscape ecology and rural development.